Strategi Pengelolaan Pasar Modern Berbasis Lingkungan Di Pasir Pengaraian - Sutami Sutami; Sofyan Husein Siregar; Trisla Warningsih (Pelantar Press, 2023)
Pasir Pengaraian Modern Market is a traditional market, said to be modern because one of the market visions is the realization of a traditional market with modern nuances that are clean, orderly, beautiful, safe, comfortable, and superior facilities in the economic movement of the Pasir Pengaraian community. The current state of the Modern Market has management conditions that tend to be less considered in the environmental, social and economic fields. The purpose of this study is to analyze the environmental conditions in the Pasir Pengaraian Modern Market, identify potentials and obstacles in the management of the Pasir Pengaraian Modern Market, and formulate a management strategy for the Modern Market in Pasir Pengaraian. This research uses a survey method, which is a method that aims to collect data from a number of variables in a community group through direct interviews and guided by the questions that have been provided. Using primary and secondary data types and sources, data collection techniques with observation techniques and in-depth interviews with informants. Determination of informants using purpose sampling techniques, including market managers as many as 7 respondents, traders as many as 40 respondents and buyers as many as 43 respondents. The strategy preparation analysis in this study uses a SWOT analysis approach. The results showed that the Modern Market is in quadrant I by applying an aggressive strategy. Quadrant I is a very favorable situation where the Pasir Pengaraian Modern Market has strengths and opportunities that can be utilized continuously to develop and improve the management of the Pasir Pengaraian Modern Market.